Analisis Ekonomi Terhadap Aspek Kesejahteraan Masyarakat di Kabupaten Halmahera Tengah - Usman Amiruddin Guanen (Jurnal Pendidikan dan Ekonomi (JUPEK), 2021)
The economic structure of a region can be seen through the size of the role of each business field in the total GRDP. This indicator is important information to determine the category of business fields which are the main support for the economy in a region. Presentation of indicators of economic structure from time to time can show whether there is a change in the economic structure of a region. Important indicators to determine regional macroeconomic conditions are data and information on the growth of gross regional domestic product (GRDP), namely gross regional domestic product (based on current prices (ADHB) and gross domestic product at constant prices (ADHK). Meanwhile, to determine the growth rate economy is by looking at data on GDP growth at constant prices. The economic structure of Central Halmahera Regency still relies on the primary sector, namely the agricultural sector, government sector, then the trade sector, mining and mining sectors followed by the hotel and restaurant sector. The aggregate derivatives are presented in two versions of valuation, namely on the basis of current prices, referred to as current prices because all aggregates are valued using prices in the current year. u year in a particular area. Central Halmahera PDRB based on the current price in 2016 was recorded at 1,769,299.61 million rupiah. Central Halmahera GRDP at constant prices in 2016 amounted to 1,262,007.71 million rupiah. The economic growth of Central Halmahera Regency in 2016 was minus 11.25.